THE IMPROVEMENT OF EARLY CHILDHOOD CREATIVITY THROUGH CARVING ACTIVITY - Nofiyanti, Indah; Tasu?ah, Neneng (Jurusan PGPAUD FIP UNNES, 2019)
In this study, there are differences in the creativity of early childhood after the application of carving art activities in the TK Negeri (State Kindergarten) Pembina of Karanganyar District, Pekalongan Regency. This study aims to determine the improvement of the creativity of early childhood through carving activity in the Kindergarten of the Pembina District of Karanganyar District, Pekalongan Regency. The subject of this study is a group B of TK Negeri Pembina of Karanganyar District. The method in this study is experimental design through the Pretest-Posttest One Group. The research activity is carried out during 12 meetings. The sample in this study amounted to 30 children in the group B class. The method of data collection used in this study is a quantitative method in the form of the questionnaire, observation, and documentation. The data analysis technique uses descriptive analysis technique. Based on statistical calculations, the t test obtains the value of t count > t table, that is 18.78 > 2.024) with sig = 0,000. The results are Ho is rejected and Ha is accepted then. So, there is a significant difference between increasing the creativity of early childhood before and after application of carving activity. This means that the hypothesis is accepted, that is, the child after carving art activity implementation has higher creativity improvement than the child before applying the carving art activities.